Crystal structure of 6,9-diamino-2-ethoxyacridinium 3,5-dinitrobenozate — dimethylsulfoxide — water (1/1/1), C24H27N5O9S - Mirocki Artur (Zeitschrift für Kristallographie - New Crystal Structures)
C24H27N5O9S, triclinic, P1‾$\overline{1}$ (no. 2), a = 7.5749(4) Å, b = 10.0368(5) Å, c = 17.9111(10) Å, α = 87.224(4)°, β = 83.678(4)°, γ = 85.414(4)°, V = 1348.04(12) Å3, Z = 2, Rgt(F) = 0.0562, wRref(F2) = 0.1477, T = 295(2) K.